KARAKTERISASI MINYAK SELAMA PEMATANGAN BUAH PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) VARIETAS DxP SIMALUNGUN - Sujadi Sujadi; Hasrul Abdi Hasibuan; Meta Rivani (Jurnal Penelitian Kelapa Sawit, 2017)
This research was conducted to study the changing levels of oil, kernel and water on the palm fruits, palm kernel oil content on the kernel, and chlorophyll, carotene and tocols (tocopherols & tocotrienols) content on oil from oil palm plants D × P Simalungun during ripening fruits for 0 to 24 weeks after reseptic (WAR). Fruits fertilized at 0 WAR containing 81% water, 0.5% oil and not containing the kernel. Water levels declined during ripening of fruits and at 20 – 24 WAR by 27 – 36%. Levels of oil rised during ripening fruits and increased rapidly after 17 WAR, maximum oil content (51.6%) was obtained at 22 WAR, which was the optimum time for harvesting the fruits. Kernel had not formed until 4 WAR and formed in 5 WAR (0.1%), the increase occurred in the 14 – 24 WAR by 4 – 5%. Changes in fatty acid shown by the total unsaturated fatty acids (polyunsaturated) decreased, while total saturated fatty acids increased. Changes in the main fatty acids were palmitic (C16:0), linoleic (C18:2), oleic (C18:1), linolenic acid (C18:3) and stearic (C18:0). Changes in fatty acids also cause changed of iodine value. Carotene had been established at 0 WAR (73 ppm) and then continue rised to 12 MSR reach 1,301 ppm and decreased during fruit ripening at 20 – 24 WAR (703 – 598 ppm). Tocols levels continue rised and a drastic improvement occurred at 20 WAR (700.3 ppm from 353 ppm at 19 WAR). Chlorophyll content increased at 0 – 16 WAR (1.7 to 20.9 ppm), and then decreased at 22 – 24 WAR (1.1 to 2.1 ppm). Palm kernel oil content in the kernel at 7 WAR amounted to 56.2% and increased to 15 WAR (56.2 to 68.7%) but decreased at 20 – 24 WAR (54.0 to 59.9%).